The Pen Is Mightier . . . - Patrick M. Lloyd, DDS, MS (Blackwell Synergy, 2000)
I got a rush when I finally read it in print, even though I wasn’t first author. It had taken 2 years to get it ‘‘on paper,’’ but there it was, in black and white, for the whole world to read (Haselton DR, Lloyd PM, Johnson WT: A comparison of the effects of two burs on endodontic access in all-ceramic high leucite crowns. Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2000;89:486-492)! Well, maybe not the whole world, but certainly the whole dental world would have access to it. And it was going to be there for a long, long time. It would outlast me, my coauthors, and all the faculty and students inmycollege